2021
DOI: 10.3390/jcm10040874
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Progression and Mortality in Patients with Prevalent Rheumatoid Arthritis and Interstitial Lung Disease: A Prospective Cohort Study

Abstract: Objectives: To describe a prospective cohort of patients with rheumatoid arthritis associated with interstitial lung disease (RA-ILD) and identify risk factors associated with disease progression and mortality in this cohort. Patients and methods: We performed a multicenter, prospective, observational study of patients with RA-ILD receiving disease-modifying antirheumatic drugs (DMARDs) between 2015 and 2020. The patients were assessed using high-resolution computed tomography and pulmonary function tests at b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 51 publications
1
40
0
1
Order By: Relevance
“…These results are similar or even superior to those observed in other cohorts of patients with ILD-SAI [5,[40][41][42]. This improvement is probably associated with increased use of specific immunosuppressants and biologics [43,44]. Furthermore, the predominance of patients with RA (followed by SS and IM) reflects the prevalence reported for each of these diseases elsewhere [45].…”
Section: Discussionsupporting
confidence: 76%
“…These results are similar or even superior to those observed in other cohorts of patients with ILD-SAI [5,[40][41][42]. This improvement is probably associated with increased use of specific immunosuppressants and biologics [43,44]. Furthermore, the predominance of patients with RA (followed by SS and IM) reflects the prevalence reported for each of these diseases elsewhere [45].…”
Section: Discussionsupporting
confidence: 76%
“…Of the patients without respiratory restriction at the initial diagnosis, about 10% of them had developed severe restrictive disorder over the 5 years [29]. Mena-Vázquez et al reported in 2021 that 19.8% of RA-ILD patients had experienced progression (worsening of FVC of >10% or DLCO of >15% and radiological progression) over the 5 years from their ILD diagnosis [30]. These patients were classified as having progressive fibrosing ILD (PF-ILD) [31,32].…”
Section: Disease Behaviormentioning
confidence: 99%
“…The independent predictors of worsening of RA-ILD were reported to be the usual interstitial pneumonia (UIP) pattern, lowered FVC (e.g., <80%), cigarette smoking, and higher anticitrullinated protein antibody titers [20,25,30,33]. Mena-Vázquez et al reported that treatment with abatacept (ABT) as a synthetic analog of CTLA-4Ig, tocilizumab (TCZ) as an interleukin-6 inhibitor (IL-6i), and rituximab (RTX) as an anti-CD20 chimeric antibody was associated with predictors of stabilized pulmonary function [30]. Factors significantly related to mortality in RA were male sex, older age, having ILD, and higher articular activity [5].…”
Section: Predictors Of Ild Progression and Prognostic Factorsmentioning
confidence: 99%
“…However, one meta-analysis did not report a higher frequency of respiratory adverse effects [14]. As for biologic DMARDS (bDMARDs), the available evidence-based mainly on cross-sectional and retrospective studies-suggests that rituximab and abatacept could be safe for CTD-ILD treatment [6,[15][16][17][18][19][20][21][22]. Tocilizumab has also been suggested to be effective in preserving lung function in SS [23].…”
Section: Introductionmentioning
confidence: 99%
“…However, some recent retrospective studies suggest that it could be an alternative treatment for patients with CTD-ILD, even in cases that prove refractory to conventional immunosuppressants [6,21,[26][27][28]. Therefore, based on a multicenter registry study of patients with CTD-ILD [21,22], we prospectively evaluated the use of rituximab with the following objectives: (1) to report on the efficacy and safety profile of rituximab in different CTD-ILDs; and (2) to identify risk factors that help to predict progression and mortality in patients treated with rituximab.…”
Section: Introductionmentioning
confidence: 99%